Analysis of rockburst driving mechanism based on unbalanced force. Issue 3 (October 2021) - Li, C Y; Xie, F S; Qin, P X; Zhang, Y; Yang, Q; Liu, Y R; Li, Z S
Abstract: Rockburst is a sudden disaster that occurs during the underground excavation. It is still challenging to predict the rockburst quantitatively. In the underground excavation, the complex geological structures, the mechanical properties of rock mass, the shape of the excavation and the construction process have an important influence on the occurrence and extent of the rockburst. Nonlinear finite element analysis can model these influencing factors comprehensively and efficiently. However, it is very difficult to analyze the overall stability of the system based on the nonlinear finite element method, and the quantitative indicators for rockburst prediction based on the nonlinear finite element analysis are rare. According to the deformation reinforcement theory, the distribution of unbalanced force during the structural deformation indicates the potential damage zone and its distance from the unbalanced state to the equilibrium. It can also be considered as the driving force of the non-equilibrium evolution of rock mass. In this paper, the physical mechanism and prediction of rockburst are both explored based on the nonlinear finite element analysis using the concept of the unbalanced force. The distribution of unbalanced force during tunnel excavation is modeled considering the geological structures and in-situ stress field. The sensitivity analysis of case studies with changing ratio between horizontal and vertical in-situ stress, inner and outer layer stiffness, and fault dip angle is conducted. Unbalanced force distribution accords with the conclusion of strength theory and stiffness theory and can be used to explore strain rockburst and strain-structure slip rockburst. The unbalanced force can reflect the driving mechanism of rockburst and can be employed as the driving force of rockburst.